Lithium disilicate glass ceramics, preparation method thereof and dental restoration
By using the lithium dissisiate glass ceramics with reasonably matched components such as SiO2, Li2O, ZrO2, etc. in dental restoration materials, the problems of long sintering time and insufficient strength of existing dental restoration materials are solved, and direct cutting processing without sintering is achieved, and good cutting performance and fracture toughness are achieved.
Patent Information
- Application Number
- CN202310420956.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-04-19
AI Technical Summary
Existing dental restorative materials need to be sintered after cutting, which is prone to deformation for a long time, and the commercially available sintered products are insufficient in strength and light transmittance after cutting, which limits their application range.
A lithium dissisite glass ceramic is provided, which is equipped with components such as SiO2, Li2O, ZrO2, etc. Through a reasonable heat treatment process, lithium dissisite glass ceramics without sintering are prepared, with good cutting performance and fracture toughness.
Lithium disilicate glass ceramics that can be directly cut without sintering are realized, shortening the waiting time of "chair-side operation", avoiding deformation and non-fitting, and also having good fracture toughness and appropriate hardness and light transmittance.
Smart Images

Figure CN116409935B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass ceramics, and in particular to a lithium disilicate glass ceramic, a preparation method thereof, and a dental restoration. Background Art
[0002] Lithium disilicate crystals have a suitable light refractive index and good biocompatibility, so lithium disilicate glass-ceramics have been increasingly used in dental restorations in recent years. Lithium silicate glass-ceramics materials, especially when the ceramic block uses lithium metasilicate as the main crystal phase, can be processed using CAD / CAM to achieve "chairside operation", but incompletely crystallized lithium metasilicate glass-ceramics generally do not have the appearance of real teeth and need to be cut and then sintered to form lithium disilicate before they can be used. The sintering time is long and requires a long wait. Some restorations are also prone to deformation during the sintering process. Therefore, in the research of dental restorations, products that do not require sintering after cutting are a research trend.
[0003] At present, the products that are available on the market and do not require sintering after cutting tend to be resin and glass-ceramic composite materials. The advantage is that no sintering is required, which shortens the time for chairside consultation. However, this type of material still has some defects, such as low strength (only between 130MPa and 200MPa), and studies have shown that the light transmittance of resin-ceramic composite materials is not as good as that of glass-ceramic, which greatly limits the scope of use of resin-ceramic composite materials. There is also a method to prepare lithium disilicate glass-ceramic by adding an emulsifier to the formula and combining it with a two-sintering process. After cutting to make the restoration embryo, no further sintering is required, and a higher strength (275MPa to 333MPa) can be achieved. However, this method only focuses on improving the strength performance of the material, and does not focus on the cutting performance and fracture toughness of the material. Summary of the invention
[0004] Based on this, the present application provides a lithium disilicate glass ceramic and a preparation method thereof and a dental restoration. The lithium disilicate glass ceramic does not require sintering, can be directly cut and processed, has good cutting performance, is easy to cut and process, has a smooth cutting surface, and has good fracture toughness.
[0005] The first aspect of the present application provides a lithium disilicate glass ceramic, which comprises the following components by weight percentage:
[0006] 58% to 68% SiO2, 3% to 6% K2O, 14% to 18% Li2O, 0.6% to 3% Al2O3, 2.5% to 5% P2O5, 8.1% to 14% ZrO2, 0.5% to 2.5% Na2O, 0.5% to 3.5% CeO2, 0.5% to 3% MgO and 0.2% to 2.5% ZnO.
[0007] In one embodiment, the lithium disilicate glass ceramic comprises the following components by weight percentage:
[0008] 60% to 67.5% SiO2, 3.4% to 4.5% K2O, 14% to 15.5% Li2O, 0.6% to 1.5% Al2O3, 2.5% to 3.5% P2O5, 8.1% to 13.5% ZrO2, 1% to 1.5% Na2O, 0.5% to 2.5% CeO2, 1% to 2% MgO and 0.2% to 1.5% ZnO.
[0009] In one of the embodiments, the composition further comprises 0.01% to 3% B2O3 by weight.
[0010] In one embodiment, the component further comprises 0.01% to 3% of a colorant by weight.
[0011] In one embodiment, the lithium disilicate glass ceramic has one or more of the following characteristics:
[0012] (1) The average three-point bending strength of the lithium disilicate glass ceramic is 200 MPa to 240 MPa;
[0013] (2) The diameter of the grains in the lithium disilicate glass ceramic is 200 nm to 900 nm;
[0014] (3) The fracture toughness of the lithium disilicate glass ceramic is 2.5 to 3.2 MPa·m 1 / 2 ;
[0015] (4) The hardness of the lithium disilicate glass ceramic is 6200MPa to 7300MPa;
[0016] (5) The transmittance of the lithium disilicate glass ceramic is 30% to 55%.
[0017] In a second aspect of the present application, a method for preparing the lithium disilicate glass ceramics according to the first aspect is provided, comprising the following steps:
[0018] Weigh raw materials according to the composition of the lithium disilicate glass ceramic;
[0019] The raw materials are mixed, melted and formed to prepare a glass block;
[0020] The glass block is subjected to annealing, nucleation treatment, first heat treatment and second heat treatment to prepare the lithium disilicate glass ceramic;
[0021] Wherein, the temperature of the first heat treatment is 610°C to 700°C, and the temperature of the second heat treatment is 800°C to 850°C.
[0022] In one embodiment, the melting conditions include: a temperature of 1400° C. to 1600° C. and a time of 60 min to 300 min.
[0023] In one embodiment, the annealing conditions include: a temperature of 400° C. to 500° C. and a time of 30 min to 90 min.
[0024] In one embodiment, the nucleation conditions include: a temperature of 500° C. to 600° C. and a time of 60 min to 360 min.
[0025] In one embodiment, the first heat treatment lasts for 1 min to 120 min, and the second heat treatment lasts for 1 min to 20 min.
[0026] The third aspect of the present application provides a dental restoration comprising the lithium disilicate glass ceramics described in the first aspect.
[0027] The above lithium disilicate glass ceramics are prepared by rationally matching the components, wherein SiO2 and Li2O are the main raw materials for forming the lithium disilicate crystal phase, and a relatively high proportion of ZrO2 and a specific range of Na2O, P2O5, MgO and ZnO are added to improve the conversion rate (content) and crystal size of lithium disilicate crystals and lithium metasilicate crystals, so that the prepared lithium disilicate glass ceramics do not need to be sintered, can be directly cut and processed, and have good cutting performance, are easy to cut, have a smooth cutting surface, and have good fracture toughness. Specifically, the advantages of the above lithium disilicate glass ceramics are as follows:
[0028] (1) It can be directly cut and polished for use without re-sintering. On the one hand, it shortens the waiting time for "chairside operation" and on the other hand, the restoration will not deform or not fit properly, and the edge adhesion is good. In addition, the equipment is easy to process, which can greatly reduce costs and is conducive to expanding the clinical application of lithium disilicate glass ceramics.
[0029] (2) It has good fracture toughness and suitable hardness, which makes the cutting performance better, the cutting surface is smooth, and the cutting edge integrity is good;
[0030] (3) The transmittance is adjustable within the range of 30% to 55%, and it is semi-transparent, which can well simulate the light transmittance and color of natural teeth;
[0031] (4) The production process is simple, with a high controllability and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is an electron microscope image of the lithium disilicate glass ceramic prepared in Example 1;
[0033] Figure 2 This is a photo of a dental crown made of lithium disilicate glass ceramics prepared in Example 1;
[0034] Figure 3 This is a photo of the cutting surface of the lithium disilicate glass ceramic prepared in Comparative Example 1 after cutting;
[0035] Figure 4 This is a photo of the cutting surface of the lithium disilicate glass ceramic prepared in Comparative Example 2 after cutting;
[0036] Figure 5 These are comparison photos of the cutting surfaces of the lithium disilicate glass ceramics prepared in Comparative Example 1 (A) and Example 1 (B) after cutting. DETAILED DESCRIPTION
[0037] The lithium disilicate glass ceramics and the preparation method thereof and the dental restoration of the present application are further described in detail below in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0039] As used herein, "one or more" refers to any one, any two, or any two or more of the listed items.
[0040] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0041] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0042] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0043] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0044] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0045] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0046] Some examples of the present application provide a lithium disilicate glass ceramic, which includes the following components by weight percentage:
[0047] 58% to 68% SiO2, 3% to 6% K2O, 14% to 18% Li2O, 0.6% to 3% Al2O3, 2.5% to 5% P2O5, 8.1% to 14% ZrO2, 0.5% to 2.5% Na2O, 0.5% to 3.5% CeO2, 0.5% to 3% MgO and 0.2% to 2.5% ZnO.
[0048] Specifically, the weight percentage of SiO2 includes but is not limited to: 58%, 59%, 60%, 60.5%, 61%, 61.5%, 62%, 62.5%, 63.2%, 64%, 64.5%, 65%, 65.5%, 66%, 66.5%, 67.2%, 67.5%, 68%.
[0049] Specifically, the weight percentage of K2O includes but is not limited to: 3%, 3.04%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.74%, 3.8%, 4%, 4.2%, 4.5%, 5%, 5.5%, and 6%.
[0050] Specifically, the weight percentage of Li2O includes but is not limited to: 14%, 14.2%, 14.5%, 14.6%, 14.8%, 15.1%, 15.3%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%.
[0051] Specifically, the weight percentage of Al2O3 includes but is not limited to: 0.6%, 0.8%, 1%, 1.06%, 1.2%, 1.5%, 2%, 2.5%, and 3%.
[0052] Specifically, the weight percentage of P2O5 includes but is not limited to: 2.5%, 2.6%, 2.7%, 2.9%, 3%, 3.2%, 3.5%, 4%, 4.5%, and 5%.
[0053] Specifically, the weight percentage of ZrO2 includes but is not limited to: 8.1%, 8.2%, 8.5%, 9%, 9.5%, 9.7%, 10%, 10.5%, 11%, 11.3%, 11.5%, 12%, 12.5%, 13%, 13.5%, and 14%.
[0054] Specifically, the weight percentage of Na2O includes but is not limited to: 0.5%, 0.8%, 1%, 1.1%, 1.2%, 1.23%, 1.25%, 1.4%, 1.5%, 2%, 2.2%, and 2.5%.
[0055] Specifically, the weight percentage of CeO2 includes but is not limited to: 0.5%, 0.6%, 0.7%, 0.75%, 0.8%, 0.85%, 0.91%, 0.98%, 1.1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, and 3.5%.
[0056] Specifically, the weight percentage of MgO includes but is not limited to: 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.55%, 1.6%, 1.65%, 1.69%, 1.7%, 1.75%, 1.8%, 2%, 2.5%, and 3%.
[0057] Specifically, the weight percentage of ZnO includes but is not limited to: 0.2%, 0.5%, 0.8%, 0.9%, 0.94%, 0.96%, 0.98%, 1%, 1.2%, 1.5%, 2%, and 2.5%.
[0058] It can be understood that the sum of the weight percentages of all components in the lithium disilicate glass-ceramic should satisfy 100%.
[0059] In some examples, the lithium disilicate glass ceramic comprises the following components by weight percentage:
[0060] 60% to 67.5% SiO2, 3.4% to 4.5% K2O, 14% to 15.5% Li2O, 0.6% to 1.5% Al2O3, 2.5% to 3.5% P2O5, 8.1% to 13.5% ZrO2, 1% to 1.5% Na2O, 0.5% to 2.5% CeO2, 1% to 2% MgO and 0.2% to 1.5% ZnO.
[0061] In some examples, the lithium disilicate glass ceramics further include 0.01% to 3% B2O3 by weight. By adding a certain range of B2O3, it is beneficial to improve the network structure of the glass and improve its fracture toughness. Specifically, the weight percentage of B2O3 includes but is not limited to: 0.01%, 0.1%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 1%, 1.32%, 1.36%, 1.38%, 1.5%, 1.8%, 2%, 2.5%, 3%.
[0062] In some examples, the lithium disilicate glass ceramics also include 0.01% to 3% colorant by weight. By adding a certain range of colorants, the color of the material can be adjusted to obtain a color close to natural teeth. Specifically, the weight percentage of the colorant includes but is not limited to: 0.01%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.19%, 2.5%, 3%. It can be understood that the type of colorant may not be particularly limited and can be reasonably selected according to the required color. Without limitation, the colorant may include V2O5, Tb4O7, Er2O3, Fe2O3, Eu2O3, Pr6O 11 , MnO2 and TiO2.
[0063] In some examples, the crystalline phase of the lithium disilicate glass ceramic includes lithium disilicate and lithium metasilicate, and also includes a glass phase.
[0064] As described above, the lithium disilicate glass ceramic has relatively fine grains, suitable hardness, high fracture toughness, and appropriate light transmittance. Without limitation, the lithium disilicate glass ceramic satisfies one or more of the following characteristics:
[0065] (1) The average three-point bending strength of the lithium disilicate glass ceramic is 200 MPa to 240 MPa;
[0066] (2) The diameter of the grains in the lithium disilicate glass ceramic is 200 nm to 900 nm;
[0067] (3) The fracture toughness of the lithium disilicate glass ceramic is 2.5 to 3.2 MPa·m 1 / 2;
[0068] (4) The hardness of the lithium disilicate glass ceramic is 6200MPa to 7300MPa;
[0069] (5) The light transmittance of the lithium disilicate glass ceramic is 30% to 55%.
[0070] Some other examples of the present application also provide a method for preparing the lithium disilicate glass ceramic as described above, comprising the following steps:
[0071] Weigh raw materials according to the composition of the lithium disilicate glass ceramic;
[0072] The raw materials are mixed, melted and formed to prepare a glass block;
[0073] The glass block is subjected to annealing, nucleation treatment, first heat treatment and second heat treatment to prepare the lithium disilicate glass ceramic;
[0074] Wherein, the temperature of the first heat treatment is 610°C to 700°C, and the temperature of the second heat treatment is 800°C to 850°C.
[0075] Specifically, the temperature of the first heat treatment includes but is not limited to: 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, and 700°C.
[0076] In some examples, the first heat treatment time is 1 min to 120 min. Specifically, the first heat treatment time includes but is not limited to: 1 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0077] Specifically, the temperature of the second heat treatment includes but is not limited to: 800°C, 810°C, 820°C, 830°C, 840°C, and 850°C.
[0078] In some examples, the second heat treatment lasts for 1 to 20 minutes. Specifically, the second heat treatment lasts for 1 to 20 minutes, including but not limited to 1 minute, 2 minutes, 4 minutes, 6 minutes, 8 minutes, 10 minutes, 15 minutes, and 20 minutes.
[0079] In addition, it can be understood that the mixing method is ball milling.
[0080] In some examples, the melting conditions include: a temperature of 1400° C. to 1600° C. and a time of 60 min to 300 min.
[0081] Specifically, the melting temperature includes but is not limited to: 1400°C, 1450°C, 1500°C, 1550°C, 1600°C.
[0082] Specifically, the melting time includes but is not limited to: 60 min, 80 min, 100 min, 120 min, 140 min, 200 min, and 300 min.
[0083] In some examples, the annealing conditions include: a temperature of 400° C. to 500° C. and a time of 30 min to 90 min.
[0084] Specifically, the annealing temperature includes but is not limited to: 400°C, 420°C, 440°C, 460°C, 480°C, and 500°C.
[0085] Specifically, the annealing time includes but is not limited to: 30 min, 40 min, 50 min, 70 min, and 90 min.
[0086] In some examples, the nucleation conditions include: a temperature of 500° C. to 600° C. and a time of 60 min to 360 min.
[0087] Specifically, the nucleation temperature includes but is not limited to: 500°C, 520°C, 540°C, 560°C, 580°C, and 600°C.
[0088] Specifically, the nucleation time includes but is not limited to: 60 min, 80 min, 100 min, 150 min, 200 min, 250 min, 300 min, and 360 min.
[0089] Some other examples of the present application also provide a dental restoration, comprising the lithium disilicate glass ceramic as described above. Further, the dental restoration is an embedded restoration material, such as an intra-coronal restoration, an inlay, an onlay, a veneer, and the like.
[0090] The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available products.
[0091] Example 1
[0092] This embodiment is a lithium disilicate glass ceramic, the components of which are shown in Table 1 (mass percentage %), and the preparation method is as follows:
[0093] (1) Weigh the raw materials (analytical grade) according to the components in Table 1, wherein potassium oxide and lithium oxide are introduced from potassium carbonate and lithium carbonate respectively, phosphorus pentoxide is introduced from ammonium dihydrogen phosphate, boron oxide is introduced from boric acid, and sodium oxide is introduced from sodium carbonate. The remaining raw materials are silicon dioxide, aluminum oxide, zirconium oxide, cerium oxide, magnesium oxide, and zinc oxide;
[0094] (2) ball milling the raw materials in step (1) for 8 h to mix them evenly, and degassing them in a muffle furnace;
[0095] (3) placing the material from step (2) into a high temperature melting furnace and melting at 1500° C. for 2 h;
[0096] (4) pouring and demolding the molten material of step (3);
[0097] (5) annealing the glass block demolded in step (4) at 420° C. for 0.5 h;
[0098] (6) nucleating the material annealed in step (5) at 520° C. for 3 h;
[0099] (7) heat treating the material after nucleation in step (6) at 630° C. for 1 h;
[0100] (8) The material after the heat treatment in step (7) is further heat treated at 820° C. for 4 minutes to prepare the lithium disilicate glass ceramic.
[0101] The preparation methods of the lithium disilicate glass ceramics of Examples 2 to 5 and Comparative Examples 1 to 4 are the same as those of Example 1, the main difference being that the mass percentages of the components are different, as specifically shown in Table 1 (mass percentage %).
[0102] Table 1
[0103] <![CDATA[SiO2]]> <![CDATA[K2O]]> <![CDATA[Li2O]]> <![CDATA[Al2O3]]> <![CDATA[P2O5]]> <![CDATA[ZrO2]]> <![CDATA[Na2O]]> <![CDATA[B2O3]]> <![CDATA[CeO2]]> MgO ZnO Pigments Example 1 61 3.74 15.1 1.06 2.9 9.7 1.25 1.38 0.98 1.7 1 0.19 Example 2 63.2 3.6 14.6 1 3 8.2 1.2 1.36 1.1 1.7 0.98 0.06 Example 3 60.0 3.7 14.8 1 2.9 11.3 1.23 1.36 0.91 1.69 0.96 0.15 Example 4 58.0 3.04 14.5 1 2.7 13.5 1.2 1.32 2 1.65 0.94 0.15 Example 5 66.2 3.3 14 1 2.55 8.1 1.08 0.5 0.8 1.45 0.88 0.14 Comparative Example 1 65.2 3.8 15.4 1.07 2.9 5.1 1.27 1.39 0.98 1.7 1 0.19 Comparative Example 2 64.9 3.78 15.3 1.1 3.9 4.5 1.26 1.4 0.98 1.7 1 0.18
[0104] Example 6
[0105] This embodiment is a lithium disilicate glass ceramic, and its preparation method is the same as that of Example 1, the main difference being that the heat treatment temperatures in steps (7) and (8) are different. Specifically, the heat treatment temperature in step (7) is 610°C, and the heat treatment temperature in step (8) is 840°C.
[0106] The preparation method is as follows:
[0107] (1) Weigh the raw materials (analytical grade) according to the components in Table 1, wherein potassium oxide and lithium oxide are introduced from potassium carbonate and lithium carbonate respectively, phosphorus pentoxide is introduced from ammonium dihydrogen phosphate, boron oxide is introduced from boric acid, and sodium oxide is introduced from sodium carbonate. The remaining raw materials are silicon dioxide, aluminum oxide, zirconium oxide, cerium oxide, magnesium oxide, and zinc oxide;
[0108] (2) ball milling the raw materials in step (1) for 8 h to mix them evenly, and degassing them in a muffle furnace;
[0109] (3) placing the material from step (2) into a high temperature melting furnace and melting at 1500° C. for 2 h;
[0110] (4) pouring and demolding the molten material of step (3);
[0111] (5) annealing the glass block demolded in step (4) at 420° C. for 0.5 h;
[0112] (6) nucleating the material annealed in step (5) at 520° C. for 3 h;
[0113] (7) heat treating the material after nucleation in step (6) at 610° C. for 1 h;
[0114] (8) The material after the heat treatment in step (7) is further heat treated at 840° C. for 4 minutes to prepare the lithium disilicate glass ceramic.
[0115] Example 7
[0116] This embodiment is a lithium disilicate glass ceramic, and its preparation method is the same as that of Example 1, the main difference being that the heat treatment temperatures in steps (7) and (8) are different. Specifically, the heat treatment temperature in step (7) is 670°C, and the heat treatment temperature in step (8) is 800°C.
[0117] The preparation method is as follows:
[0118] (1) Weigh the raw materials (analytical grade) according to the components in Table 1, wherein potassium oxide and lithium oxide are introduced from potassium carbonate and lithium carbonate respectively, phosphorus pentoxide is introduced from ammonium dihydrogen phosphate, boron oxide is introduced from boric acid, and sodium oxide is introduced from sodium carbonate. The remaining raw materials are silicon dioxide, aluminum oxide, zirconium oxide, cerium oxide, magnesium oxide, and zinc oxide;
[0119] (2) ball milling the raw materials in step (1) for 8 h to mix them evenly, and degassing them in a muffle furnace;
[0120] (3) placing the material from step (2) into a high temperature melting furnace and melting at 1500° C. for 2 h;
[0121] (4) pouring and demolding the molten material of step (3);
[0122] (5) annealing the glass block demolded in step (4) at 420° C. for 0.5 h;
[0123] (6) nucleating the material annealed in step (5) at 520° C. for 3 h;
[0124] (7) heat treating the material after nucleation in step (6) at 670° C. for 1 h;
[0125] (8) The material after the heat treatment in step (7) is further heat treated at 800° C. for 4 minutes to prepare the lithium disilicate glass ceramic.
[0126] Test example:
[0127] (1) Average value of three-point bending strength: tested in accordance with GB30367-2013;
[0128] (2) Fracture toughness: tested according to the single edge V-notch beam (SEVNB) method;
[0129] (3) Hardness: Tested in accordance with GB / T 16534-2009 Test method for room temperature hardness of fine ceramics (Vickers hardness tester test);
[0130] (4) Transmittance: tested using a haze meter;
[0131] (5) Grain diameter: tested by SEM scanning electron microscope;
[0132] (6) Cutting performance: The lithium disilicate glass ceramics prepared in the examples and comparative examples were cut and polished (without sintering) according to existing processing methods to produce dental crowns, and the roughness of the surfaces of the dental crowns was observed.
[0133] The test results are shown in Table 2 below:
[0134] Table 2
[0135]
[0136] In addition, the SEM scanning electron microscope image of Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the crystal grains of microcrystalline glass are small, and the diameter of the grains is 250nm to 700nm.
[0137] The lithium disilicate glass ceramic prepared in Example 1 was cut and polished (without sintering) to form a crown, as shown in the photo. Figure 2 As shown, it can be seen that the cutting surface is smooth and the cutting edge is complete. Figures 3 to 5 The comparison photos of the cutting surfaces of Comparative Examples 1 and 2 and Comparative Example 2 and Example 1 show that Comparative Examples 1 and 2 use different ZrO2 contents based on Example 1, which not only reduce the fracture toughness, but also make cutting difficult and the cutting surface after cutting is rough.
[0138] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0139] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the patent application. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A lithium disilicate glass ceramic, characterized in that: In terms of weight percentage, it includes the following components: 58% to 68% SiO2, 3% to 6% K2O, 14% to 18% Li2O, 0.6% to 3% Al2O3, 2.5% to 5% P2O5, 8.1% to 14% ZrO2, 0.5% to 2.5% Na2O, 0.5% to 3.5% CeO2, 0.5% to 3% MgO, 0.2% to 2.5% ZnO and 0.01% to 3% B2O3; The diameter of the grains in the lithium disilicate glass ceramic is 250nm to 700nm; The lithium disilicate glass ceramic is used for preparing dental restorations by direct cutting without sintering.
2. The lithium disilicate glass ceramic according to claim 1, characterized in that: In terms of weight percentage, it includes the following components: 60% to 67.5% SiO2, 3.4% to 4.5% K2O, 14% to 15.5% Li2O, 0.6% to 1.5% Al2O3, 2.5% to 3.5% P2O5, 8.1% to 13.5% ZrO2, 1% to 1.5% Na2O, 0.5% to 2.5% CeO2, 1% to 2% MgO, 0.2% to 1.5% ZnO and 0.5% to 1.5% B2O3.
3. The lithium disilicate glass ceramic according to claim 1, characterized in that: In terms of weight percentage, the components also include 0.01% to 3% of colorant.
4. The lithium disilicate glass ceramic according to any one of claims 1 to 3, characterized in that: The lithium disilicate glass ceramic has one or more of the following characteristics: (1) The average three-point bending strength of the lithium disilicate glass ceramic is 200 MPa to 240 MPa; (2) The fracture toughness of the lithium disilicate glass ceramic is 2.5 to 3.2 MPa·m 1 / 2 ; (3) The hardness of the lithium disilicate glass ceramic is 6200MPa to 7300MPa; (4) The transmittance of the lithium disilicate glass ceramic is 30% to 55%.
5. The method for preparing the lithium disilicate glass ceramic according to any one of claims 1 to 4, characterized in that: The steps include: Weigh raw materials according to the composition of the lithium disilicate glass ceramic; The raw materials are mixed, melted and formed to prepare a glass block; The glass block is subjected to annealing, nucleation treatment, first heat treatment and second heat treatment to prepare the lithium disilicate glass ceramic; Wherein, the temperature of the first heat treatment is 610°C to 700°C, and the temperature of the second heat treatment is 800°C to 850°C.
6. The method for preparing lithium disilicate glass ceramics according to claim 5, characterized in that: The melting conditions include: a temperature of 1400° C. to 1600° C. and a time of 60 min to 300 min.
7. The method for preparing lithium disilicate glass ceramics according to claim 5, characterized in that: The annealing conditions include: a temperature of 400° C. to 500° C. and a time of 30 min to 90 min.
8. The method for preparing lithium disilicate glass ceramics according to claim 5, characterized in that: The nucleation conditions include: a temperature of 500° C. to 600° C. and a time of 60 min to 360 min.
9. The method for preparing lithium disilicate glass ceramics according to any one of claims 5 to 8, characterized in that: The time of the first heat treatment is 1 min to 120 min, and the time of the second heat treatment is 1 min to 20 min.
10. A dental restoration, characterized in that: The invention comprises the lithium disilicate glass ceramics as described in any one of claims 1 to 4.
11. The dental restoration according to claim 10, characterized in that The lithium disilicate glass ceramic does not require a sintering process after cutting to prepare the dental restoration.
Citation Information
Patent Citations
Tooth repair material as well as preparation method and application thereof
CN104609730A
High-strength and high-permeability lithium disilicate glass ceramic as well as preparation method and application thereof
CN113501668A
High-strength and high-transmittance lithium disilicate glass ceramic, and preparation method therefor and application thereof
WO2023011105A1